2003
DOI: 10.3141/1837-07
|View full text |Cite
|
Sign up to set email alerts
|

Design of Granular Pavement Layers Considering Climatic Conditions

Abstract: A new simple design approach that uses test results from the repeated load triaxial apparatus to establish the risk level of permanent deformations in the unbound granular layers (UGL) in pavement constructions under consideration of the seasonal effects was developed. From these data, a serviceability limit line (plastic shakedown limit) stress boundary for the unbound granular materials (UGM) was defined for different moisture contents. Below this line, the material has stable behavior. The serviceability li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…The influence of water content on the mechanical behaviour of granular materials under cyclic loading has been observed experimentally in several studies [39][40][41][42]. The results obtained in this study on the interlayer soil are in agreement with these works.…”
Section: Mechanical Behavioursupporting
confidence: 82%
“…The influence of water content on the mechanical behaviour of granular materials under cyclic loading has been observed experimentally in several studies [39][40][41][42]. The results obtained in this study on the interlayer soil are in agreement with these works.…”
Section: Mechanical Behavioursupporting
confidence: 82%
“…Among the environmental factors affecting the permanent deformation of unbound layers of flexible pavements, many researchers found that the effect of water content is of great importance (Arnold and al. 2002;Werkmeister and al. 2003;Cracium 2009;Carrera and al.…”
Section: Introductionmentioning
confidence: 94%
“…The mechanical behaviour of ballast is very important to provide (predict) safety and economy of the rail track maintenance. Large-scale triaxial tests are usually curried out to study the mechanical behaviour of ballast under monotonic and repetitive loading [1][2][3][4][5]. These large-scale triaxial tests are very expensive.…”
Section: Introductionmentioning
confidence: 99%